The Moderating Role of Self-Efficacy in the Relationship Between ICT Literacy and Students’ Self-Concept in Inquiry-Based Learning - Yanuarto, Wanda Nugroho; Anggoro, Subuh; Setyaningsih, Eka; Fukui, Masanori (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study focuses on inquiry-based teaching and learning (IN), emphasizing the development of students' self-efficacy (SEDU), self-concept (PP), and information and communication technology literacy (TIK). Students are encouraged to prioritize the learning process over grades or competition, to develop a sense of competence and autonomy, and to focus on broader skill development rather than purely technical objectives. The purpose of this research was to evaluate the performance of SEDU, PP, and TIK within an IN framework. A quantitative approach with a cross-sectional survey design was employed to collect and analyze data. This study investigates the relationships among SEDU, PP, TIK, and IN. Data were collected using a structured questionnaire, and the relationships between these variables were analyzed using structural equation modeling (SEM). The sample consisted of 631 elementary school teachers and 224 mathematics education students from the University of Muhammadiyah Purwokerto, Indonesia. The analysis revealed statistically significant interactions among SEDU, PP, TIK, and IN. Additionally, SEDU was identified as a moderating factor in the interaction between PP, TIK, and IN. These findings suggest that SEDU has the potential to enhance classroom enrichment in IN settings for students with high levels of PP and TIK. This study contributes to the existing literature on instructional feedback and inquiry-based learning by providing recommendations for fostering effective IN classrooms. Specifically, it highlights the importance of enhancing students' technological competencies and personal growth to maximize the benefits of inquiry-based education.